Analyses of circular DNA molecules in the leafhopper Psammotettix alienus for identification of viruses and plasmids - Sigalla, Jeremiah (2019)
Microorganisms often depend on vectors for transmission. A single vector may carry different species of microorganisms such as fungi, bacteria and viruses. In Sweden, leafhoppers of the species Psammotettix alienus are known as a vector of wheat dwarf virus, but they may be carriers of other microorganisms as well. In this study, we analysed small circular DNA molecules in leafhopper DNA extracts for identification of viruses and plasmids. Using PCR, WDV was detected in different samples of P. alienus collected in autumn 2017 in different parts of Sweden. Using blast nucleotide analyses, sequences from cloned PCR products were found to share 99% nucleotide identity to previously sequenced WDV isolates from Sweden. Phylogenetic analysis of a genome region covering part of the replication-associated protein A gene (repA), movement protein gene (MP) and long intergenic region (LIR) (1162 nucleotides) showed that the obtained WDV isolates were closely related to the isolates previously reported from Sweden. Also, rolling circle amplification (RCA) was employed as a means of obtaining the full-length plasmids and genomes of viruses with circular DNA. However, we did not get WDV DNA by the RCA method, but circular DNA of a bacteriophage as well as plasmids of phytoplasma and bacteria, were identified. One cloned RCA product shared 83% nucleotide identity with plasmids of wheat blue dwarf phytoplasma (WBDP). A phylogenetic analysis of 1125 bp covering part of the replication-associated protein gene and non-coding DNA confirmed that the analysed sequence was closely related to WBDP plasmids reported from China. WBDP has been reported in China to cause wheat blue dwarf disease resulting in severe yield losses in wheat at different occasions. A similar disease has been reported in Sweden in past years, whereas, through transmission tests, symptoms were then observed on crop plants, such as rye, oat and barley. In addition, we identified circular DNA of a bacteriophage known as sphinx, which is reported to be similar to phages infecting bacteria of the genus Acinetobacter. Generally, the results of this study show that RCA is able to assist in detecting a range of viruses and plasmids.